PROBLEMS OF INTERACTION OF ENERGY AND ECOLOGY (British Journal of Global Ecology and Sustainable Development, 2022)
In the article types of non-traditional renewable energy sources and the main factors of their environmental impact on the natural environment and objects, information on the characteristics of electricity generation at the expense of renewable energy sources.